Análise espacial dos casos de hepatite a e óbitos por doenças isquêmicas do coração em Foz do Iguaçu - PR - Trevisol, Viviane Cristina (2017)
Developing countries experience different levels of epidemiological transition in which infectious and parasitic diseases are replaced by chronic-degenerative and anthropogenic diseases as the main cause of mortality in the population. In Brazil, due mainly to socioeconomic, health and regional differences, the epidemiological transition does not occur homogeneously in the national territory. The objective of this work was to analyze the spatial distribution of cases of hepatitis A and death due ischemic heart diseases in Foz do Iguaçu-Pr and its demographic and socioeconomic determinants and thus allowing the reflection about the epidemiological transition that occur in a Brazilian border municipality. The mean incidence rates of hepatitis A and specific mortality due to ischemic heart diseases (IHD) in Foz do Iguaçu-PR, from 2010 to 2015, were used, considering the census tracts of the municipality as analysis unit. The data were obtained from the Epidemiology Sector of the city of Foz do Iguaçu-PR. The georeferencing of hepatitis A cases and IHD deaths were performed using the QGIS program, version 2.16. The spatial data exploratory analysis was performed through the Global Moran analysis, Local Indicator of Spatial Association (LISA) analysis and Global Moran Bivariate analysis, using the GeoDa program, version 1.6.7. As results, a significant positive spatial autocorrelation (p = 0.001) was detected when the census tracts were analyzed according to the hepatitis A incidence rate and the specific mortality rate by IHD. The incidence rate of hepatitis A presented a mean of 9.48 cases/100,000 inhabitants and the specific mortality rate due to IHD, referring to the period, presented an average of 29.4 deaths/100,000 inhabitants. Through the LISA analysis, four high-high clusters were identified considering the incidence of hepatitis A and were distributed in the North, South and East districts of the municipality, while for IHD mortality, seven high-high clusters were identified, distributed in the Eastern, West, South and North, but in comparison to the clusters referring to the incidence of hepatitis A, these census tracts had a different geographic location. In the Moran Global bivariate analysis, variables related to a lower socioeconomic 9 and sanitary conditions showed a positive correlation with high rates of hepatitis A incidence, while variables related to a higher socioeconomic and sanitary pattern had a positive correlation with high specific mortality rates for DIC. The data of the present study indicate that Foz do Iguaçu presents urban areas whose conditions favor the transmission and maintenance of high rates of hepatitis A, coexisting with urban areas where better socioeconomic and sanitary conditions prevail where ischemic heart diseases predominate, suggesting that the municipality is still in a prolonged and polarized phase of the epidemiological transition.